Hasil Rapat Penelaahan Program KB Nasional Propinsi Kalimantan Tengah, tahun 1985/1986 (Badan Koordinasi Keluarga Berencana Nasional, Propinsi Kalimantan Tengah, 1985)
On the review of the 1985/1986 national family planning program to be implemented in Central Kalimantan Province; proceedings of meeting.